A rise by any other name?: sensitivity of growth regressions to data source - Jan Hanousek; Dana Hájková; Randall Filer (Center for Economic Studies and ifo Institute (CESifo), 2007)
Measured rates of growth in real per capita income differ drastically depending on the data source. This phenomenon occurs largely because data sets differ in whether and how they adjust for changes in relative prices across countries. Replication of several recent studies of growth determinants shows that results are sensitive in important ways to the choice of data. Previous warnings against using data adjusted to increase cross-country comparability to study within-country patterns over time (growth rates) have been largely ignored at the cost of possibly contaminating the conclusions.
Keywords: C82; O47; 330; Wirtschaftswachstum; Regression; Statistischer Fehler; Relativer Preis; Messung; Theorie; Schätzung; Welt